Avaliação do tratamento com Probiatop® na mucosite intestinal induzida por 5-fluorouracil em camundongos - Fernanda Carvalho de Souza (2023)
Gastrointestinal mucositis is an inflammatory condition that affects the mucosa of the gastrointestinal tract and can occur as a common side effect of chemotherapy treatment, including the use of drugs such as 5-fluorouracil (5-FU). Currently, there are no curative treatments, but only palliative interventions that seek to improve the quality of life of these patients. In this context, probiotic microorganisms are increasingly used as alternatives to protect the gastrointestinal mucosa against this side effect and associated disorders. This study aimed to evaluate the effect of treatment with Probiatop®, composed of Lactobacillus acidophilus SD5221, Lacticaseibacillus rhamnosus SD5675, Lacticaseibacillus paracasei SD5275 and Bifidobacterium lactis SD5674, on experimental intestinal mucositis induced by 5-FU. For the protocol execution, female Balb/c mice (6-8 weeks) and mucositis induced in a single intraperitoneal dose of 5-FU (300 mg/Kg i.p) were used. Clinical, microbiological, immunological, histological and physiological parameters were analyzed. In our results, it was observed that Probiatop® decreased the weight loss induced by 5-FU, improved the integrity of the epithelial barrier, reducing intestinal permeability and bacterial translocation. In addition, it improved histological scores, decreased the inflammatory cell infiltrate and expression of pro-inflammatory cytokines, mitigating the inflammatory response, but was unable to improve the clinical parameters measured by the disease activity index (DAI) of the animals compared to the mucositis control group and did not induce an increase in sIgA. Therefore, it is concluded that Probiatop® was able to decrease the damage caused by mucositis induced by 5-FU.